Smart mobility solutions in public transport based on analysis chosen smart cities - Dudycz, Helena; Piątkowski, Igor (Mobilność inteligentna w transporcie publicznym na podstawie analizy wybranych miast inteligentnych, 2018)
The term smart city is increasingly used in media and across society. Every city wants to have the status of a smart city, because it means using smart solutions to help the city with contemporary problems related to, inter alia, public transport. For the inhabitants of these cities, the implementation of the smart city concept may mean a higher level of quality of life and greater comfort of life. The main goal of this paper is the presentation of the results of the conducted study on what cities should do and how, in order to improve the quality of public transport in their city to become a smart city. Based on comparative analysis of public transport of the best smart cities in the world i.e. London, San Francisco and Singapore, this research aims at pointing out the development direction of implementing smart mobility for cities. The selected cities will be examined and compared according to the following criteria: availability of transport in the city, applied technologies in transport solutions, and the strategy for the development of transport services in the city
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 2 (48), s. 19-35
Keywords: smart city; smart mobility; public transport; information and communication technologies; ICT; miasto inteligentne; mobilność inteligentna; transport publiczny; technologie informacyjno-komunikacyjne